Multiple-Rusophycus assemblage from the Parnaíba Basin (NE Brazil) reflects trilobites as tracemakers and molting behavior - Sedorko, Daniel; de Barros, Gabriel E. B.; Netto, Renata Guimarães; Ghilardi, Renato Pirani; Agostinho, Sônia; Ramos, Kimberly Silva; Franco Neto, Emmanuel; Moreira Junior, Carlos Alves; Borghi, Leonardo (Frontiers in Ecology and Evolution, 2023)
Trilobites inhabited all environments of Paleozoic seas, ranging from estuaries to continental slopes, and were globally distributed. Although their functional morphology and phylogenetic relations are established by well-preserved body fossils, the behavior of trilobites has received less attention. Three well-known trace fossils are interpreted to be produced by trilobitomorphs when preserved in Paleozoic rocks, Rusophycus (a resting trace), Cruziana (a furrowing trace), and Diplichnites (a locomotion trace). Those trace fossils unveil some aspects of trilobite behavior, but they were not investigated to test paleoecologic strategies based on morphometric parameters. This study uses Rusophycus to access the paleoecologic strategies of trilobites in storm-dominated shallow marine deposits of the Pimenteira and Cabeças formations (Middle to Upper Devonian, Parnaíba Basin, Brazil). It was conducted a detailed analysis of the Rusophycus specimens in a section that represents the transition between the Pimenteira and Cabeças formations (Parnaíba Basin). The width and length of the Rusophycus were measured, and statistical analyses were performed to understand the population characteristics. Relatively small-sized Rusophycus are dominant in such deposits, suggesting the dominance of young tracemakers and inferred r-strategist populations. The here reported multiple-Rusophycus assemblage reveals paleoecologic strategies of the population, and tiers relationship (cross-cutting epistratal and shallow-tier trace fossils such as Bergaueria, Palaeophycus, and Protopaleodictyon) indicate deep Rusophycus. The main reason for those burrowing activities deep in the substrate might be protection during ecdysis. Thus, the random distribution, lack of hunting evidence, and depth of Rusophycus suggest molting activity as the trigger for their production in storm-influenced beds of the Pimenteira Formation, probably by calmoniids or homalonotids.